(untitled) (Innovaciones Educativas, 2021)
The Self-Assessment Commissions (CAE) play a leading role in the development of the self-assessment processes, for accreditation purposes, carried out by the undergraduate and postgraduate careers of the School of Education Sciences (ECE), which have with the accreditation granted by the National Accreditation System for Higher Education (SINAES) of Costa Rica; Therefore, to demonstrate this role, the opinions of the people who make them up were investigated, about the work methodology, participation and communication, and the competencies and training of these commissions. The methodological option selected to describe the opinions was quantitative, for which a questionnaire was used. The results reflect a positive perception towards the raison d’être and the impact of the self-evaluation processes, in the quest to achieve accreditation. There are slight differences in opinions, concerning the methodology; Although, people consider the methods, techniques, and resources used to collect information to be reliable and valid; They also question its quantitative and limiting character for the participation of the protagonists, as in the case of teachers and students. Furthermore, they argue that the methodology is poorly adjusted to the UNED context. Regarding the participation and communication that is generated; as well as with the competencies and training of the CAE, results are shown those show aspects that also need to be addressed.